Internal Control Analysis of Hospital Logistics to Support Operational Efficiency at UGM Academic Hospital - Suradi; Erni Saharuddin (Indonesian Journal Publisher, 2026)
Hospital logistics management plays an important role in supporting healthcare services and operational efficiency. Ineffective internal control may lead to inventory discrepancies, procurement delays, and inefficient use of supplies. This study aims to analyze the internal control of housekeeping supply management at UGM Academic Hospital based on the COSO framework and to identify challenges in its implementation. The study applies the COSO framework to housekeeping supply management in a hospital setting and provides empirical evidence on how its components support effective inventory management. A qualitative research approach was employed, with data collected through interviews, observations, and document analysis involving administrative staff, warehouse personnel, procurement officers, and representatives from service units. Data were analyzed using the five components of the COSO internal control framework: control environment, risk assessment, control activities, information and communication, and monitoring activities. The findings indicate that internal control has been implemented through planning, procurement, storage, distribution, and inventory monitoring. However, several challenges remain, including inventory counting that is not integrated with service units, procurement delays, off-system supply requests, and discrepancies between inventory records and actual stock levels. Strengthening an integrated inventory system, enhancing procurement evaluation, and conducting regular inventory monitoring are recommended to improve the effectiveness of internal control and hospital operational efficiency.